Augustus and his smile - Rayner, Catherine; Arnold, Annie (Little Tiger Press London, 2006)
Augustus the tiger has lost his smile. He sets out to find it and begins a journey that takes him all over the world through dense jungles, arid deserts, and deep oceans. By the time his journey finally comes to an end, Augustus has realised that he will never be without his smile again.